login
Solution of the complementary equation a(n) = a(n-1) + 2*a(n-2) + b(n-2), where a(0) = 1, a(1) = 3, b(0) = 2, b(1) = 4, and (a(n)) and (b(n)) are increasing complementary sequences.
5

%I #4 Nov 19 2017 19:06:05

%S 1,3,7,17,36,76,156,317,639,1284,2574,5155,10317,20642,41292,82594,

%T 165197,330405,660820,1321652,2643315,5286643,10573298,21146610,

%U 42293233,84586481,169172976

%N Solution of the complementary equation a(n) = a(n-1) + 2*a(n-2) + b(n-2), where a(0) = 1, a(1) = 3, b(0) = 2, b(1) = 4, and (a(n)) and (b(n)) are increasing complementary sequences.

%C The increasing complementary sequences a() and b() are uniquely determined by the titular equation and initial values. See A295053 for a guide to related sequences.

%H Clark Kimberling, <a href="https://cs.uwaterloo.ca/journals/JIS/VOL10/Kimberling/kimberling26.html">Complementary equations</a>, J. Int. Seq. 19 (2007), 1-13.

%F a(n+1)/a(n) -> 2.

%e a(0) = 1, a(1) = 3, b(0) = 2, b(1) = 4

%e a(2) = a(1) + 2*a(0) + b(0) = 7

%e Complement: (b(n)) = (2, 4, 5, 6, 8, 9, 10, 11, 12, 13, 14, ...)

%t mex := First[Complement[Range[1, Max[#1] + 1], #1]] &;

%t a[0] = 1; a[1] = 3; b[0] = 2; b[1] = 4;

%t a[n_] := a[n] = a[ n - 1] + 2 a[n - 2] + b[n - 2];

%t b[n_] := b[n] = mex[Flatten[Table[Join[{a[n]}, {a[i], b[i]}], {i, 0, n - 1}]]];

%t Table[a[n], {n, 0, 18}] (* A295146 *)

%t Table[b[n], {n, 0, 10}]

%Y Cf. A295053, A295145, A295147, A295148.

%K nonn,easy

%O 0,2

%A _Clark Kimberling_, Nov 19 2017